Creative Arts Therapy in the "Remote Therapeutic Response" Format in the Education System - Shir Korman-Hacohen; Dafna Regev; Efrat Roginsky (MDPI AG, 2022)
Many creative arts therapists work in the education system on a regular basis. As a result of the pandemic, all have had to treat students in a "remote therapeutic response" format. The aim of the present study was to map creative arts therapists' perceptions of the "remote therapeutic response" in the education system. Semi-structured interviews were conducted with 15 creative arts therapists who participated in the study. The consensual qualitative research approach yielded seven domains: (1) the emotional experiences of transitioning to a remote therapeutic response; (2) the implementation of the remote therapeutic response; (3) benefits of remote creative arts therapy; (4) challenges in remote creative arts therapy; (5) remote contact with parents; (6) working in the educational system; (7) insights and recommendations. Although the findings show that creative arts therapists believe that remote creative arts therapy will never be a fully satisfactory replacement for most clients, remote work, despite its many difficulties and challenges, has also opened the door to new possibilities in the world of creative arts therapy in the education system.